Insurable Interest in Takaful: A Theoretical Contrivance for Islamic Insurers - Azeez, Yusuf Abdul; Ishola, Abdullahi Saliu (International Journal of Economics and Financial Issues, 2016)
The Takaful (Islamic Insurance) is not only a key branch of the Islamic Financial System (IFS) but also one of the important Islamic financial instruments and a strong tool for managing individual risks and business overturns. In terms of operational models, it shares some business setups with Islamic banking, and in a way, it is regarded as “a modern technical approach to Islamic banking operation”, for it evolved, like Islamic banking, from the determination of Muslims to revive the Islamic way of life, particularly in the reorganization of finance and economy; an exertion often described as a very difficult jihad: building a financial system where interest does not exist. Accordingly, this research attempts to propound some theories for assessment of insurable interest in Islamic insurance (Takaful). The theories, as analysed are intended to serve as working tools for the present and future Islamic insurers, without limitation to differences in place and space. In doing this, the work is divided into five parts. The first part introduces the study while terminology clarification is undertaking in the second part. The third part examines the legal basis for the insurable interest in Takaful, while the conceptual precepts for the development and application of the theories are taken up in the fourth part with certain relevant study inferences forming the concluding part. Keywords: Takaful; Islamic Banking; Islamic Insurance; Islamic Financial System JEL Classification: G2